Distinct Dynamic and Conformational Features of Human STING in Response to 2′3′‐cGAMP and c‐di‐GMP - Guo, Jingjing; Wang, Jie; Fan, Jingrong; Zhang, Yan; Dong, Wenpei; Chen, Chang‐Po (Chembiochem : a European journal of chemical biology, 2019)
The human stimulator of interferon genes protein (hSTING) can bind cyclic dinucleotides (CDNs) to activate the production of type I interferons and inflammatory cytokines. These CDNs can be either bacterial secondary messengers, 3′3′‐CDNs, or endogenous 2′3′‐cGAMP. cGAMP, with a unique 2′–5′ bond, is the most potent activator of hSTING among all CDNs. However, current understanding of the molecular principles underlying the unique ability of 2′3′‐cGAMP to potently activate hSTINGs other than 3′3′‐CDNs remains incomplete. In this work, molecular dynamics simulations were used to provide an atomistic picture of the binding of 2′3′‐cGAMP and one 3′3′‐CDN (c‐di‐GMP) to hSTING. The results suggest that hSTING binds more strongly to 2′3′‐cGAMP than to c‐di‐GMP, which prefers to bind with a more open and flexible state of hSTING. Finally, a potential “dock–lock–anchor” mechanism is proposed for the activation of hSTING upon the binding of a potent ligand. It is believed that deep insights into understanding the binding of hSTING with 3′3′‐CDNs and the endogenous 2′3′‐cGAMP would help to establish the principles underlying powerful 2′3′‐cGAMP signaling and the nature of hSTING activation, as well as related drug design. Biting back! The human stimulator of interferon genes protein (hSTING) can bind cyclic dinucleotides (CDNs) to activate the production of type I interferons and inflammatory cytokines. Molecular dynamics simulations are used to provide an atomistic picture of the binding of 2′3′‐cGAMP and one 3′3′‐CDN (c‐di‐GMP) to hSTING.